Isolation of Vibrionaceae from wild blue mussel (Mytilus edulis) adults and their impact on blue mussel larviculture. Issue 4 (15th March 2017) - Eggermont, Mieke; Bossier, Peter; Pande, Gde Sasmita Julyantoro; Delahaut, Vyshal; Rayhan, Ali Md.; Gupta, Nipa; Islam, Shikder Saiful; Yumo, Elsie; Nevejan, Nancy; Sorgeloos, Patrick; Gomez-Gil, Bruno; Defoirdt, Tom
Abstract: The blue mussel ( Mytilus edulis ) is known as a robust bivalve species, although its larviculture appears to be highly susceptible to diseases. In this study, we isolated 17 strains from induced mortality events in healthy wild-caught blue mussel adults and demonstrated that they caused between 17% and 98% mortality in blue mussel larvae in a newly developed, highly controlled immersion challenge test model. Eight of the isolates belong to the Splendidus clade of vibrios, while the other isolates belong to the genus Photobacterium . The genomes of the most virulent Vibrio isolate and the most virulent Photobacterium isolate were sequenced and contained several genes encoding factors that have previously been linked to virulence towards bivalves. In vitro tests confirmed that all 17 isolates were positive for these virulence factors. The sequenced genomes also contained a remarkably high number of multidrug resistance genes. We therefore assessed the sensitivity of all isolates to a broad range of antibiotics and found that there were indeed many strong positive correlations between the sensitivities of the isolates to different antibiotics. Our data provide an ecological insight into mass mortality in blue mussels as they indicate that wild mussels contain a reservoir of pathogenic bacteria. Abstract : Vibrionaceae were isolated from mass mortality events in wild-caught blue mussels, and were (highly) pathogenic in a newly developed, highly controlled challenge test with blue mussel D-larvae.